0407 Early Efficacy With Once-Nightly Sodium Oxybate (ON-SXB; FT218): Post-hoc Analyses From REST-ON. (25th May 2022) - Krahn, Lois; Roy, Asim; Winkelman, John; Morse, Ann Marie; Seiden, David; Dubow, Jordan; Gudeman, Jennifer
Abstract: Introduction: Extended-release once-nightly sodium oxybate (ON-SXB; FT218) is in development for adults with narcolepsy. In REST-ON, significant improvements on the Maintenance of Wakefulness test, Clinical Global Impression of Improvement rating, and number of weekly cataplexy episodes occurred with all analyzed ON-SXB doses vs placebo (week 3, 6-g dose; week 8, 7.5-g dose; week 13, 9-g dose; all P<0.001). ON-SXB was superior to placebo on Epworth Sleepiness Scale (ESS) score and sleep quality and refreshing nature of sleep using visual analog scales (VAS; all P<0.001). ON-SXB 4.5 g significantly reduced cataplexy episodes vs placebo at week 1 (P<0.05). Post hoc analyses investigated ON-SXB efficacy on ESS score, VAS sleep quality, and VAS refreshing nature of sleep at weeks 1 and 2. Methods: Participants in the double-blind, phase 3 REST-ON (NCT02720744) trial were ≥16 years old, had narcolepsy type 1 or 2, and were randomized 1:1 to ON-SXB (4.5 g, 1 week; 6 g, 2 weeks; 7.5 g, 5 weeks; 9 g, 5 weeks) or placebo. Participants recorded ESS scores and VAS for sleep quality and refreshing nature of sleep (1-100; 1=poor quality/unrefreshing sleep; 100=good quality/refreshing sleep) using electronic diaries. P-values were calculated using a mixed-effects model for repeated measures in the modified intent-to-treat (mITT) population (ie, participants receiving ≥1 dose of study drug having ≥1 efficacy assessment at week 3). Results: In the mITT population (n=190; ON-SXB, n=97; placebo, n=93), baseline ESS scores were 16.6 and 17.5 with ON-SXB and placebo, respectively. At week 2, ESS score was significantly improved with ON-SXB vs placebo (P<0.02) with numerical improvement seen at week 1. At baseline, sleep quality was 53.8 and 55.9 on VAS in the ON-SXB and placebo groups, respectively, and baseline refreshing nature of sleep was 46.5 and 49.9. At weeks 1 and 2, sleep quality (P<0.01; P<0.001) and refreshing nature of sleep (P<0.05; P=0.001) were significantly improved for ON-SXB vs placebo. Conclusion: Improvement in daytime sleepiness, sleep quality, and refreshing nature of sleep occurred with ON-SXB beginning the first week of treatment. Some patients may experience early narcolepsy symptom relief with ON-SXB. Support (If Any): Avadel Pharmaceuticals